2022
DOI: 10.1007/s00246-022-02881-5
|View full text |Cite
|
Sign up to set email alerts
|

Ventricular Arrhythmias and Sudden Death Following Percutaneous Pulmonary Valve Implantation in Pediatric Patients

Abstract: Reports have suggested a transient increase in ventricular ectopy early after percutaneous pulmonary valve implantation (PPVI). Little is known about the potential for more serious ventricular arrhythmias (VA) in children who undergo PPVI. We sought to evaluate the incidence of severe VA following PPVI in a pediatric population and to explore potential predictive factors. A retrospective cohort study was conducted of patients who underwent PPVI under 20 years of age in our institution from January 2007 to Dece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…While ventricular arrhythmia occurrence is common following TPVR in the nRVOT, our data suggest that this is a benign and transient phenomenon. The periprocedural ventricular arrhythmias evaluated in this study likely have a different mechanism from the late occurring severe ventricular arrhythmias reported recently in this population 11 . Only 61.5% of patients with ventricular arrhythmia were treated.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…While ventricular arrhythmia occurrence is common following TPVR in the nRVOT, our data suggest that this is a benign and transient phenomenon. The periprocedural ventricular arrhythmias evaluated in this study likely have a different mechanism from the late occurring severe ventricular arrhythmias reported recently in this population 11 . Only 61.5% of patients with ventricular arrhythmia were treated.…”
Section: Discussionmentioning
confidence: 57%
“…8 A recent cohort study reported a late occurrence of severe ventricular arrhythmias following TPVR in this population. 11 This underscores the need for additional pediatric data to inform guidelines and protocols for ventricular arrhythmia surveillance and management following TPVR.…”
Section: Introductionmentioning
confidence: 99%